2019
DOI: 10.1111/tpj.14369
|View full text |Cite
|
Sign up to set email alerts
|

Keep calm and carry on: miRNA biogenesis under stress

Abstract: Summary MicroRNAs (miRNAs) are major post‐transcriptional regulators of gene expression. Their biogenesis relies on the cleavage of longer precursors by a nuclear localized processing machinery. The evolutionary preference of plant miRNAs to silence transcription factors turned these small molecules into key actors during growth and adaptive responses. Furthermore, during their life cycle plants are subject to changes in the environmental conditions surrounding them. In order to face these changes, plants disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 117 publications
1
36
0
4
Order By: Relevance
“…In fact, it has recently begun to emerge that a variety of environmental alterations can differently affect miRNA production and stability by directly altering the main enzymes related to their entire biogenesis pathways. In response to specific stress signals, the whole machinery associated with miRNA production can be turned down through the establishment of feedback regulatory mechanisms [44]. An excellent example is represented by 22-nt miR168 molecules that are produced instead of the 21-nt long isoforms of the same miRNA and that are preferentially complexed with AGO10 to trigger the synthesis of secondary siRNAs from AGO1 loci [134].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has recently begun to emerge that a variety of environmental alterations can differently affect miRNA production and stability by directly altering the main enzymes related to their entire biogenesis pathways. In response to specific stress signals, the whole machinery associated with miRNA production can be turned down through the establishment of feedback regulatory mechanisms [44]. An excellent example is represented by 22-nt miR168 molecules that are produced instead of the 21-nt long isoforms of the same miRNA and that are preferentially complexed with AGO10 to trigger the synthesis of secondary siRNAs from AGO1 loci [134].…”
Section: Discussionmentioning
confidence: 99%
“…The transport of these molecules within the plant and their consequent effects, including the transgenerational inheritance of epigenetic marks underlying stress memory phenomena, require further investigations to be deciphered completely [43]. Finally, another noteworthy aspect pertains to the flexible regulation of small RNA biogenesis in response to specific stress signals [44].…”
Section: Introductionmentioning
confidence: 99%
“…It also reported that miRNAs [98,99] further lead to the synthesis of secondary siRNAs called phasiRNAs and/or easiRNAs. In recent studies, it observed that the multistep process of miRNA biogenesis and degradation plays a crucial role in the "fine-tuning" of plant response to growth and development under environmental stresses [100,101]. Furthermore, it is also noticed that individual components of the miR156 biogenesis pathway such as D-body proteins like DCL1, AGO (Argonaut), HYL 1, SE, DRB2 (Double-stranded RNA binding proteins-2) and miRNA-miRNA* duplex, and their interactome also plays a crucial role to produce a final response at the plant level to external as well as internal perturbations, [102].…”
Section: Biogenesis and Action Of The Mir156mentioning
confidence: 99%
“…Recent evidence indicates that AGO proteins respond to environmental stimuli (Manavella et al, 2019). The direct involvement of plant AGO proteins in biotic interactions is also well known, mainly for plant defense against bacteria and virus (Raja et al, 2008; Carbonell and Carrigton, 2015; Fátyol et al, 2016).…”
Section: Argonaute Proteins In Symbiosismentioning
confidence: 99%